2022
DOI: 10.1155/2022/9730753
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness and Safety of Abelmoschus manihot in Treating IgA Nephropathy: A Systematic Review and Meta-Analysis

Abstract: Introduction. IgA nephropathy (IgAN) is a common issue. In China, Abelmoschus manihot (AM) is widely used in the treatment of IgAN. However, their combined effectiveness and safety for this purpose have not yet been explored. AM is an effective medicine for treating IgAN. This meta-analysis aimed to evaluate the effectiveness of AM for IgAN. Materials and Methods. The Cochrane Library, PubMed, EMBASE, Allied and Complementary Medicine Database (AMED), Chinese Biomedical Literature Database (CBM), Chinese Natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…However, the values of change in estimated GFR and serum creatinine from baseline to the end of treatment were not statistically significant among the three groups [ 2 ]. In addition, a systematic evaluation and meta-analysis with 850 participants showed that the combination of A.manihot and RAS inhibitors significantly improved proteinuria compared to RAS inhibitors, that A.manihot was generally well tolerated and did not increase the incidence of adverse events [ 6 ]. A multicenter randomized, double-blind, parallel-controlled clinical trial with 413 participants showed that the combination of A.manihot and irbesartan apparently reduced the excretion of albuminuria and proteinuria in type 2 diabetic patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, the values of change in estimated GFR and serum creatinine from baseline to the end of treatment were not statistically significant among the three groups [ 2 ]. In addition, a systematic evaluation and meta-analysis with 850 participants showed that the combination of A.manihot and RAS inhibitors significantly improved proteinuria compared to RAS inhibitors, that A.manihot was generally well tolerated and did not increase the incidence of adverse events [ 6 ]. A multicenter randomized, double-blind, parallel-controlled clinical trial with 413 participants showed that the combination of A.manihot and irbesartan apparently reduced the excretion of albuminuria and proteinuria in type 2 diabetic patients.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple clinical studies have found that HKC combined with ACEI/ARB is more effective than ACEI/ARB alone in treating CKD. However, more attention has been paid to chronic glomerulonephritis (Dai et al, 2022) or IgA nephropathy (Jia et al, 2022) from these studies. In recent years, HKC combined with ACEI/ARB has been more widely used for treating DKD in clinical practice, and lots of novel data evaluating HKC in DKD have been published.…”
mentioning
confidence: 99%